STRATEGI GENERASI PESONA INDONESIA (GENPI) PANDEGLANG DALAM MEMPROMOSIKAN KEARIFAN LOKAL (LOCAL WISDOM) (Studi Deskriptif Pada Destinasi Digital Pasar Kaulinan Menes) - Eka Darisnadi; Damanhuri Damanhuri; Ronni Juwandi (Universitas Sultan Ageng Tirtayasa, 2021)
This study aims to describe how the strategy of the GenPI Pandeglang community in promoting local wisdom in the Menes Kaulinan Market Digital Destination. The subjects of this study were the Head of the Tourism Destination Division of the Banten Province Tourism Office, the Manager of Kaulinan Market Management Menes, the Chairperson of the GenPI Pandeglang community, the Head of the Pandeglang GenPI community online team, the Chair of the Pandeglang GenPI community creative team and the Menes Kaulinan Market visitor. This study uses a qualitative approach with descriptive methods. Data collection techniques used are interviews, observation and documentation. The data analysis used was data collection, data reduction, data presentation and conclusion drawing. The validity of the data was done by triangulating sources, triangulating techniques and member checks. The results of the study found that the efforts made by the GenPI Pandeglang community in promoting local wisdom included planning, implementation and evaluation aspects. The obstacles faced are personal factors and situational factors. The response of visitors to the Menes Kaulinan Market is in the form of the enthusiasm of visitors by playing traditional games, buying culinary snacks at the Kaulinan Menes Market and visitor responses in the form of likes, comments, shares and retweets on the social media accounts of the Menes Kaulinan Market.